سلطات الضبط الإقتصادي في القانون الجزائري - أسامة هني; فتحي تكريت (My University, 2018)
Abstract: The state' schoice of retreatingfrom the economical Field isconsidered to bestrategicbothpolitically and economically, after what have resulted of the many crises in all aspects ,whichobligedit to impose new and radical transformations and devote a legaltoolis considered to be a new face of the state. represented by the authority 'seconomic control. The independent administration institutions isconsidered to be an alternative to the traditional administration institutions in the economical and financialfield; it has been given missions and wideauthor itiessuch as the control fonction -preventive- represented by the organisations , decisions,and recommendations and also a consultant body of the state , this in addition to the semi legal mission by judging to put an end to disputes between economical dealers and imposing penalties in order to maintain the respect of regulations . It canbesaidthat the authority'seconomi control is a legal and successful way to regulate the economicalactivities in the market,keeping in consideration the balance between the public institutions and the other hand the interests of the clients and the public interest. .......................... Résumé L’option de retrait de l’État du champ économique est stratégique aux deux niveaux Politique et économique, imposé par de multiples crises dans tous les domaines, inévitablement L’imposition de réformes radicales et la consécration d’un instrument juridique qui est une nouvelle manifestation et un nouveau visage de l’État: Pouvoirs de contrôle économique. Les organes administratifs indépendants sont une alternative aux organes administratifs traditionnels dans le domaine économique et Les finances se sont vu confier de vastes fonctions et pouvoirs, y compris la fonction de surveillance de l’émission des règlements, des décisions et des recommandations, ainsi que l’organe consultatif de l’État. Cela s’ajoute à la fonction quasi judiciaire de l’arbitrage en tant qu’organe de résolution des litiges entre clients économiques, et à la fonction d’introduction de sanctions en tant qu’outil répressif pour faire respecter les réglementations et législations applicables.